Direito é luta: o legado do Pronera para uma educação socialmente referenciada - Maia, Maria Claudia Zaratini (2019)
This thesis deals with the right of the rural population to education, especially the access to higher education in law courses, through the public policy called Pronera - National Program of Education in Agrarian Reform. Pronera It was created by the social movements of the countryside. In 2006, started the first law course through Pronera, at the Federal University of Goiás, with formation of the first class in 2012. In 2013, two new classes began in the State of Bahia. In addition to the three groups mentioned, there are three other Pronera Law classes in progress, one at the Federal University of Paraná, the other at the Federal University of Goiás and the Federal University of South and Southeast Pará. The research analyzes these courses and their impact. in guaranteeing the rights of the rural population, if they have the possibility to train organic professionals to their social classes and if the specificities of the Course can contribute to legal education. To this end, a bibliographic and documentary research and interviews were conducted with the coordinators and students of the courses. The method used was dialectical historical materialism, more suitable for understanding concrete reality. The conclusions are that the courses make possible the access to the Law Course for the rural population, despite the small number of vacancies still offered, and the difficulties still faced, with the pedagogy of alternation and the limitation of resources, which contribute to there is counter-hegemonic legal education, as opposed to traditional legal education, which has the possibility of training organic professionals to their social classes, committed to the realization of rights and social justice.